The expanding role of 16s ribosomal RNA PCR in the management of patients with infective endocarditis undergoing cardiac surgery - Pavone, Natalia; Cammertoni, Federico; Calabrese, Maria; Bruno, Piergiorgio; Scoppettuolo, Giancarlo; Lombardo, Antonella; Giovannenze, Francesca; Taddei, Eleonora; Fiori, Barbara; D’Inzeo, Tiziana; Cutrone, Gessica; Iannaccone, Giulia; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundAetiological diagnosis and targeted antibiotic therapy are essential to improve the prognosis of patients with infective endocarditis. Molecular tests on blood have been reported to be effective in identifying the causative organism and are recommended when blood cultures are negative. The role of molecular tests on the surgically excised valve is still unclear and needs further investigation.Materials and methodsIn this prospective, observational, single center study, we enrolled 100 consecutive patients with native or prosthetic valve endocarditis who underwent cardiac surgery between April 2020 and June 2023. Results of preoperative blood cultures, valve culture, 16s ribosomal RNA and histopathologic analysis of surgical samples were collected in a dedicated database.ResultsThe mean age of the study population was 60 ± 12.5 years, with a majority of men (73%). Previous cardiac surgery was reported in 31% of patients. Blood culture, valve culture, and 16srRNA were positive in 83%, 47%, and 76% of cases, respectively. The sensitivity of both valve culture and 16srRNA decreased significantly with prolonged preoperative antibiotic therapy. Of note, 16srRNA was the only positive result in 7% of cases, allowing aetiological diagnosis. In 33% of patients, the valve culture test was negative while the molecular test was positive. In these cases, histopathological analysis showed acute inflammation in most cases. In 10%, the molecular test helped in resolving discrepancies between the results of blood and valve cultures.ConclusionsThe molecular test showed significantly higher diagnostic sensitivity than valve culture and maintained this efficacy even after 28 days of preoperative antibiotic therapy. In addition to identifying the pathogen in 7% of cases with negative culture results, the molecular test demonstrated utility in other crucial situations. When valve cultures were negative, combining molecular testing and histopathological analysis they allowed the identification of patients who could benefit from prolonged antibiotic therapy. In addition, molecular testing guided the choice of antibiotic treatment when there was a discrepancy between blood culture and valve culture results. Based on these findings, molecular testing should be considered in all patients with infective endocarditis undergoing cardiac surgery. Clinical Trial Registration: ClinicalTrials.gov, identifier (NCT05791357).